Cerebellar soluble mutant ataxin-3 level decreases during disease progression in Spinocerebellar Ataxia Type 3 mice. - Huu Phuc Nguyen; Jeannette Hübener; Jonasz Jeremiasz Weber; Stephan Grueninger; Olaf Riess; Andreas Weiss (PLoS ONE, 2013)
Spinocerebellar Ataxia Type 3 (SCA3), also known as Machado-Joseph disease, is an autosomal dominantly inherited neurodegenerative disease caused by an expanded polyglutamine stretch in the ataxin-3 protein. A pathological hallmark of the disease is cerebellar and brainstem atrophy, which correlates with the formation of intranuclear aggregates in a specific subset of neurons. Several studies have demonstrated that the formation of aggregates depends on the generation of aggregation-prone and toxic intracellular ataxin-3 fragments after proteolytic cleavage of the full-length protein. Despite this observed increase in aggregated mutant ataxin-3, information on soluble mutant ataxin-3 levels in brain tissue is lacking. A quantitative method to analyze soluble levels will be a useful tool to characterize disease progression or to screen and identify therapeutic compounds modulating the level of toxic soluble ataxin-3. In the present study we describe the development and application of a quantitative and easily applicable immunoassay for quantification of soluble mutant ataxin-3 in human cell lines and brain samples of transgenic SCA3 mice. Consistent with observations in Huntington disease, transgenic SCA3 mice reveal a tendency for decrease of soluble mutant ataxin-3 during disease progression in fractions of the cerebellum, which is inversely correlated with aggregate formation and phenotypic aggravation. Our analyses demonstrate that the time-resolved Förster resonance energy transfer immunoassay is a highly sensitive and easy method to measure the level of soluble mutant ataxin-3 in biological samples. Of interest, we observed a tendency for decrease of soluble mutant ataxin-3 only in the cerebellum of transgenic SCA3 mice, one of the most affected brain regions in Spinocerebellar Ataxia Type 3 but not in whole brain tissue, indicative of a brain region selective change in mutant ataxin-3 protein homeostasis.